Downregulation of the Autism Spectrum Disorder Gene Shank2 Decreases Bone Mass in Male Mice. (15th December 2022) - Ahmad, Mubashir; Stirmlinger, Nadine; Jan, Irfana; Stifel, Ulrich; Lee, Sooyeon; Weingandt, Marcel; Kelp, Ulrike; Bockmann, Jürgen; Ignatius, Anita; Böckers, Tobias M.; Tuckermann, Jan
ABSTRACT: Mutations of the postsynaptic scaffold protein Shank2 lead to autism spectrum disorders (ASD). These patients frequently suffer from higher fracture risk. Here, we investigated whether Shank2 directly regulates bone mass. We show that Shank2 is expressed in bone and that Shank2 levels are increased during osteoblastogenesis. Knockdown of Shank2 by siRNA targeting the encoding regions for PDZ and SAM domain inhibits osteoblastogenesis of primary murine calvarial osteoblasts. Shank2 knockout mice ( Shank2 −/− ) have a decreased bone mass due to reduced osteoblastogenesis and bone formation, whereas bone resorption remains unaffected. Induced pluripotent stem cells (iPSCs)‐derived osteoblasts from a loss‐of‐function Shank2 mutation in a patient showed a significantly reduced osteoblast differentiation potential. Moreover, silencing of known Shank2 interacting proteins revealed that a majority of them promote osteoblast differentiation. From this we conclude that Shank2 and interacting proteins known from the central nervous system are decisive regulators in osteoblast differentiation. © 2022 The Authors. JBMR Plus published by Wiley Periodicals LLC on behalf of American Society for Bone and Mineral Research. Abstract : Here we show that loss of function of the postsynaptic scaffold protein Shank2 in mice is accompanied with decreased osteoblastogenesis, which subsequently reduced trabecular bone mass. Our work suggests that the higher fracture risk in patients with autism spectrum disorders (ASD) due to loss of Shank protein expression depends at least in part on the role of Shank2 in bone.